Sex in Biology, the phenomenon of intersex. Bioethical reflections from the standpoint of personhood and individual self-determination - Lorandos (Φίλιππος Λοράνδος) Filippos (Bioethica, 2019)
Sex in Biology, despite the simple dualism, which biparental reproductive mechanism implies, presents an extraordinary ‘polysemy’, and a great difficulty to be defined on exclusively biological criteria. Throughout its evolution, from unicellular eukaryotes till complex multicellular eukaryotes and humans, different forces seem to have led to the establishment of the sexually dimorphic model, involving yet numerous unfitting cases. In humans, the existence of intersex people, that is individuals whose sex characteristics to do not fit to either male or female category, has been known in most civilizations since the antiquity, often followed by prejudices and stigma. In the modern era, the scientific progress, the sociocultural transformations and the human rights fights have initiated a great ethical and legal discussion on the non-urgent medical surgeries on intersex minors and especially on intersex infants. This article, after a preview of the ‘polysemy’ and polymorphism of sex in biology, presents briefly the intersex phenomenon in humans and intersex persons’ treatment from the state and specialists, both earlier and nowadays, focusing more on Greece’s paradigm. Subsequently, an critical normative evaluation of the non-consensual, medically unnecessary operations on intersex minors from the standpoint of bioethics is attempted, drawing from fundamental principles of moral philosophy, as well as the findings of biology.